2007
DOI: 10.1093/eurheartj/ehl506
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of intrathoracic impedance monitoring to alert patients with an implanted device of deteriorating chronic heart failure

Abstract: A device-based algorithm that alerts patients in case of decreasing intrathoracic impedance facilitates the detection of HF deterioration. Future randomized, controlled trials are needed to test whether the tailored use of intrathoracic impedance monitoring can improve the ambulatory management of patients with chronic HF and an implanted device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
123
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(132 citation statements)
references
References 9 publications
7
123
1
1
Order By: Relevance
“…Vollmann et al reported that the fluid index threshold crossing alert detected clinical HF deterioration with a 60% sensitivity (95%CI 46-73) and positive predictive value of 60% (95%CI 46-73) at the nominal threshold setting of 60 ohm-days. 5 Predicting the occurrence of an arrhythmia based on a cardiac overload that may result in HF cannot exceed the accuracy of predicting clinical HF deterioration using the intrathoracic impedance system. Furthermore, arrhythmias do not always appear at the time of HF deterioration.…”
Section: Additional Considerationsmentioning
confidence: 99%
“…Vollmann et al reported that the fluid index threshold crossing alert detected clinical HF deterioration with a 60% sensitivity (95%CI 46-73) and positive predictive value of 60% (95%CI 46-73) at the nominal threshold setting of 60 ohm-days. 5 Predicting the occurrence of an arrhythmia based on a cardiac overload that may result in HF cannot exceed the accuracy of predicting clinical HF deterioration using the intrathoracic impedance system. Furthermore, arrhythmias do not always appear at the time of HF deterioration.…”
Section: Additional Considerationsmentioning
confidence: 99%
“…14,15) Of these benefi ts, the monitoring of exceeding the fl uid index threshold allows us earlier detection of pulmonary congestion than the appearance of symptoms and other clinical parameters including elevation of plasma BNP levels. 12,13) In this study, there were 10 patients with worsening heart failure defi ned as exceeding the fl uid index threshold after the earthquake. Of the 10 patients, 9 using a remote monitoring system did not require hospitalization, but 1 patient without this system was admitted to hospital due to acute decompensated heart failure, which suggests that remote monitoring of intrathoracic impedance may be a useful tool for the management of CHF patients after disasters.…”
Section: Discussionmentioning
confidence: 99%
“…11) Intrathoracic impedance monitoring has been shown to be useful for detecting pulmonary congestion and CHF worsening earlier than the appearance of symptoms and elevation of plasma levels of B-type natriuretic peptide. 12,13) Moreover, a remote monitoring system of implantable devices allows earlier detection of clinical problems including pulmonary congestion and arrhythmic events. 14,15) In areas devastated by disaster where visiting clinics is diffi cult for the patients, this system may work more effectively than under usual circumstances.…”
mentioning
confidence: 99%
“…Device-monitored parameters have been already analyzed as predictors of HF decompensation or death. Results of these analyses were discordant -non-randomized studies found device-based diagnostic features useful in predicting adverse events, but in DOT-HF randomized trial number of HF hospitalizations was higher in patients with defibrillators equipped with monitor emitting an alert indicating TI decrease [7,[11][12][13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%